The Analysis of Sales by Using Apriori and FP-Growth at PT. Panca Putra Solusindo - Anggraeni, Sita; Iha, Marlina Ana; Erawati, Wati; Khairunnas, Sayyid (Politeknik Ganesha Medan, 2019)
Panca Putra Solusindo is a company which sells Electronic equipment. It has a lot of transactions. Among these data, the company has not been able to provide such platform that can be used as information for management to find out which products are most preferred by consumers. Data mining is present to provide information patterns to companies in answering these needs and helping in marketing to be more effective. In this research, the function of the Apriori algorithm association is used to find out the minimum support and minimum confidence and FP-Growth in knowing the frequent itemset and both of them can find out the best rule that occurs in the transaction. These two algorithms are tested by using Weka application version 3.8.